Efikasi Diri dan Hasil Belajar Matematika: Meta-analisis - M. Nur Ghufron; Rini Risnawita Suminta (Buletin Psikologi, 2013)
This Study was meta-analysis of the relationship between self efficacy and mathematics learning outcome. The quantitative review includes 14 studies from 13 articles that contained a combined sample of approximately 6157. This analysis extends previous work by directly correcting error of sampling and measurements. Summary analysis provided support that self efficacy has a correlation on mathematics learning outcome. The result showed self efficacy have been identified as predictors and mathematics learning outcome.